Yellow fluorescent protein-based label-free tension sensors for monitoring integrin tension. Issue 41 (16th April 2020) - Wang, Yongliang; Wang, Han; Tran, Michael V.; Algar, W. Russ; Li, Hongbin
Abstract : Yellow fluorescent protein serves as a label-free tension sensor to monitor integrin tension. Abstract : Using enhanced yellow fluorescent protein, we demonstrate the feasibility to use fluorescent proteins as a label-free tension sensor to monitor integrin tension.